Akurasi Skor Porcel Berbasis CT Scan Toraks dengan Kontras Intravena dalam Memprediksi Efusi Pleura Maligna di Rumah Sakit Adam Malik - Atika Dalila Ginting; Netty Delvrita Lubis; Ade Rahmaini (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Malignant pleural effusion (MPE) is a significant cause of morbidity and remains diagnostically challenging because cytological examination fails to detect malignancy in approximately 25% of cases, necessitating additional diagnostic approaches. This study aimed to evaluate the diagnostic accuracy of the CT scan based Porcel score in differentiating malignant from benign pleural effusion. A cross-sectional diagnostic study was conducted in 100 patients with pleural effusion who underwent contrast-enhanced thoracic CT and cytological and/or histopathological examination at Adam Malik Hospital, Medan between January 2024 and October 2025. ROC curve analysis based on pleural fluid cytology showed limited discriminative ability (AUC = 0.591), whereas analysis using the final diagnosis demonstrated good diagnostic performance with an AUC of 0.865 (95% CI: 0.793–0.937). Using a cut-off value of ≥7, the Porcel score achieved a sensitivity of 80.8%, specificity of 81.8%, positive predictive value of 94%, negative predictive value of 54.5%, and an overall diagnostic accuracy of 81%. The CT scan based Porcel scoring system demonstrates acceptable diagnostic performance for differentiating malignant from benign pleural effusions and may serve as a useful non-invasive tool for identifying malignant pleural effusion.